Diversity Dimensions in Mathematics and Language Learning : Perspectives on Culture, Education and Multilingualism. - Fritz, Annemarie; Gürsoy, Erkan; Herzog, Moritz (Berlin/Boston : Walter de Gruyter GmbH, 2021)
The DaZ-Forschung series presents current research on the acquisition of German as a second language and on education opportunities in the context of migration and multilingualism, in the form of monographs or anthologies. The volumes range from empirical and theory-forming studies through to application-oriented articles from the fields of second language acquisition, applied linguistics, education research, language didactics and language teaching. In thematic terms the series contains articles on sociolinguistic and psycholinguistic aspects, on the structure and dynamics of learner languages, on language production and language comprehension as well as intervention studies and research on classroom teaching and conditions of language acquisition. DaZ-Forschung is the first part of the three-part series cluster that will be augmented by the DaZ Handbooks series and the DaZ Textbooks series shortly.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2024. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books